2014
DOI: 10.1002/polb.23645
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing polymers with heterogeneous micro- and macrostructures

Abstract: The potentially extreme heterogeneity of polymer micro-and macrostructures has been demonstrated and a means for characterizing them has been suggested. To ensure that all possible microstructures, such as diad stereosequences in vinyl homopolymers and monomer sequences in copolymers, including their locations along polymer chains, that is, all macrostructures, are represented, it became necessary to generate samples with huge quantities (many many tons) of constituent polymer chains. This suggested a practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The bulky ester pendant in the adduct can be selectively transformed into less bulky pendant group on demand via acidolysis and esterification. Thus, a cycle consisting of radical addition, acidolysis, and esterification could be repeated to give sequence‐controlled polymers consisting of methacrylate units …”
Section: Control Of Macromolecular Architecturementioning
confidence: 99%
“…The bulky ester pendant in the adduct can be selectively transformed into less bulky pendant group on demand via acidolysis and esterification. Thus, a cycle consisting of radical addition, acidolysis, and esterification could be repeated to give sequence‐controlled polymers consisting of methacrylate units …”
Section: Control Of Macromolecular Architecturementioning
confidence: 99%
“…We believe 4 that coalesced samples of amorphous polymers consist of small unoriented regions containing extended and largely unentangled polymer chains, because the volume of individual un-oriented crystals in the polymer-CD-IC powders are 10 times the volume of the polymer coalesced from each. Such nanostructured amorphous polymer samples, as obtained through confinement in and subsequent release from their ICs, have been observed [2][3][4] to have glass-transition temperatures, T g s, substantially elevated above their normally processed samples. This is believed to result from the closer packing of extended un-entangled coalesced chains which produce samples with higher densities.…”
mentioning
confidence: 99%
“…This procedure would result in ester bonds that are connected either to the methylene groups in AA and DEG or to the rigid virtual bonds replacing the cyclobutane and cyclohexane rings in TMCBD and DMCHC. This would allow us to utilize the RIS models developed for aliphatic polyesters whose ester groups are connected by methylene or oxyalkane sequences or phenyl groups (poly (ethylene terephthalate)) to account for the ester bonds formed by TMCBD and DMCHC.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] More recently we have extended our Kerr effect observations to polymers whose complete macrostructures were controlled and varied by careful syntheses, and found that the Kerr effect can distinguish between polymers containing the same types and quantities of short-range microstructures, as determined, for example, by 13 C-NMR, but which are located in different positions along their backbones. [33][34][35][36][37][38] For this reason, we employed Kerr effect observations of the complex aliphatic co-and homopolyesters in an attempt to begin to determine microstructures of longer range than are evidenced by NMR.…”
Section: Introductionmentioning
confidence: 99%